Advances in radiofrequency ablation of the cerebral cortex in primates using the venous system: Improvements for treating epilepsy with catheter ablation technology - Henz, Benhur D; Friedman, Paul A; Bruce, Charles J; Holmes, David R; Bower, Mark; Madhavan, Malini; DeSimone, Christopher V; Wahnschaffe, Douglas; Berhow, Steven; Danielsen, Andrew J; Ladewig, Dorothy J; Mikell, Susan B; et al. (Epilepsy research, 2014)
BACKGROUND: Pharmacology frequently fails for the treatment of epilepsy. Although surgical techniques are effective, these procedures are highly invasive. We describe feasibility and efficacy of minimally invasive mapping and ablation for the treatment of epilepsy. METHODS: Mapping and radiofrequency ablations were performed via the venous system in eleven baboons and three dogs. RESULTS: Mapping in deep cerebral areas was obtained in all animals. High-frequency pacing was able to induce seizure activity of local cerebral tissue in 72% of our attempts. Cerebral activity could be seen during mapping. Ablative lesions were deployed at deep brain sites without steam pops or sudden impedance rise. Histologic analysis showed necrosis at the sites of ablation in all primates. CONCLUSION: Navigation through the cerebral venous system to map seizure activity is feasible. Radiofrequency energy can be delivered transvenously or transcortically to successfully ablate cortical tissue in this animal model using this innovative approach.
Keywords: psi; mapování mozku; mozková kůra; Radiofrequency; studie proveditelnosti; Feasibility Studies; Cerebral cortex; Dogs; epilepsie; Catheter ablation; modely nemocí na zvířatech; Venous system; Catheter Ablation; Papio; magnetické pole; Magnetic Fields; Neurosurgical Procedures; miniinvazivní chirurgické výkony; Animals; Minimally Invasive Surgical Procedures; zvířata; Brain Mapping; neurochirurgické výkony; katetrizační ablace; Cerebral Cortex; Disease Models, Animal; Epilepsy